Job Satisfaction and Turnover Intention: are Workload and Organizational Commitment the Issue? - Ramadhania, Gita Fajar; Wulansari, Nury Ariani (Management Analysis Journal, 2022)
The aim of this study was to examine the effect of workload and organizational commitment on turnover intention through job satisfaction. The sample in this study were non-civil servant health workers at psychiatric Hospital Dr. Amino Gondohutomo. The data collection method using questionnaires. The data analysis method used were Structure Equation Model-Partial Least Square (SEM-PLS) using the SmartPLS 3.0. The results showed that workload had no effect on turnover intention while organizational commitment and job satisfaction had a negative and significant effect on turnover intention. workload has a negative and significant effect on job satisfaction, organizational commitment has a positive and significant effect on job satisfaction. Job satisfaction successfully mediates the relationship between workload and organizational commitment on turnover intention. suggestions for hospital management can reduce the workload by increasing the number of health workers. And also, in increasing organizational commitment can create a harmonious atmosphere in the environment.